The Influence of Brand Image, Brand Trust, and Brand Awareness on Purchase Intention: A Study on Generation Z Users by.U Provider in Surabaya - Visi Ari Pratiwi; Rusdi Hidayat Nugroho; Budi Prabowo; Indah Respati Kusumasari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research seeks to examine the influence of Brand Image, Brand Trust, and Brand Awareness on Purchase Intention of Generation Z users of By.U Card Providers in Surabaya. This research uses a quantitative approach with an associative research type. The sample size was 200 By.U users from Generation Z in Surabaya, with data collected through questionnaires and literature studies, and analyzed using SPSS Version 30 software. The sampling method applied was purposive sampling, and data analysis was carried out through multiple linear regression analysis. The findings indicate that simultaneously, the three variables have a significant effect on the Purchase Intention of By.U Generation Z users in Surabaya. In partial analysis, both Brand Image and Brand Awareness show a positive and significant influence, while Brand Trust does not significantly affect the Purchase Intention of By.U Generation Z users in Surabaya